Dynamics surrounding the implementation of the primary health care approach in Zimbabwe’s rural areas: the case of Mt Darwin District - Chilunjika- Muzvidziwa, Sharon R. T; Chilunjika, Alouis (International Journal of Clinical Inventions and Medical Sciences, 2022)
This research studied the implementation of the Primary Health Care approach to health service delivery in Zimbabwe’s rural areas from 2009 to 2012. The approach was launched in response to the Alma-Alta Declaration in 1978 which sought to end the inequalities in health care provision around the globe and was first adopted and implemented in 1982 in Zimbabwe. The approach almost collapsed due to the economic meltdown in the past decade but the period 2009 to 2013 marked a new economic paradigm in Zimbabwe which saw the economy being dollarized which subsequently led to the revival and the resuscitation of the health sector. It is therefore to explore the progress and the dynamics surrounding the implementation of the PHC at Mt Darwin Hospital in light of the dollarized economy. The study explores the dynamics surrounding the implementation of PHC at Mt Darwin District Hospital by particular attention to the following key elements: promotion of nutrition, sanitation, maternal and child care, immunization, treatment of common diseases and provision of essential drugs. Qualitative techniques such as face to face interviews with key informants and documentary research were used to generate data. The research findings revealed that PHC is a powerful tool in delivering health services in Mt Darwin. However, lack of material, financial and human resources have hindered the proper implementation of the PHC approach in Mt Darwin district. The study recommends multi sectoral collaboration in solving health related issues.